2022
DOI: 10.17509/jaset.v14i2.49743
|View full text |Cite
|
Sign up to set email alerts
|

Initial Returns Determinants with the Underwriter’s Reputation as a Moderating Factor

Abstract: Main purpose- The main purpose of this study is to find out the factors that affect the initial return. Accounting information and non-accounting information are components that determine the initial return that needs to be considered.Method - The population used is all companies that conducted initial public offerings (IPOs) on the Indonesia Stock Exchange (IDX) in the 2016-2020 period. In this study, the sampling technique used was non-probability sampling with a saturated sample technique of 135 companies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This research has shown that underwriter reputation can affect the relationship between asset returns and underpricing. Pangestuti (2022) asserts that the use of a reliable underwriter by the company will affect how strong the return on assets is. However, the P-Values = 0.039 < 0.05 in the statistical data indicate that H7 is accepted and supported by Pangestuti (2022) previous research.…”
Section: The Impact Of Return On Assets On Underpricing: a Moderating...mentioning
confidence: 99%
“…This research has shown that underwriter reputation can affect the relationship between asset returns and underpricing. Pangestuti (2022) asserts that the use of a reliable underwriter by the company will affect how strong the return on assets is. However, the P-Values = 0.039 < 0.05 in the statistical data indicate that H7 is accepted and supported by Pangestuti (2022) previous research.…”
Section: The Impact Of Return On Assets On Underpricing: a Moderating...mentioning
confidence: 99%